2016
DOI: 10.4014/jmb.1601.01033
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Identification of Antioxidant Peptides from Enzymatic Hydrolysate of Spirulina platensis

Abstract: The aim of this study was to isolate antioxidant peptides from an enzymatic hydrolysate of Spirulina platensis. A novel antioxidant peptide was obtained by ultrafiltration, gel filtration chromatography, and reverse-phase high-performance liquid chromatography, with the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay used to measure the antioxidant activity, and the sequence was determined to be Pro-Asn-Asn (343.15 Da) by electrospray ionization tandem mass spectrometry. This peptide was synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 36 publications
1
28
1
1
Order By: Relevance
“…However, further digestion in the intestine brought the ACE inhibitory activity of the final GI digests to 24.85±1.01-33.60±2.40 (p<0.05), indicating that some peptides with stronger ACE inhibitory activities were produced during the simulated GI digestion. Previous studies have also reported that peptides derived from rapeseed [16], egg white lysozyme [62], and ham [64] still exhibited ACE inhibitory activity after GI digestion.…”
Section: Changes In the Ace Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, further digestion in the intestine brought the ACE inhibitory activity of the final GI digests to 24.85±1.01-33.60±2.40 (p<0.05), indicating that some peptides with stronger ACE inhibitory activities were produced during the simulated GI digestion. Previous studies have also reported that peptides derived from rapeseed [16], egg white lysozyme [62], and ham [64] still exhibited ACE inhibitory activity after GI digestion.…”
Section: Changes In the Ace Inhibitory Activitymentioning
confidence: 99%
“…Enzymatic hydrolysis enables the release of these peptides which are inactive within the sequence of parent protein [14 and 15]. It has been suggested that non-protein compounds such as phenolics and pigments need to be taken into account when evaluating the antioxidant activities of some protein hydrolysates like rapeseed [16]. S. platensis contains phycobiliproteins as lightharvesting protein-pigment complexes [17].…”
Section: Introduction Spirulina Platensis a Blue-green Microalgae Bementioning
confidence: 99%
“…Generally, the scavenging activity of ultrafiltrated hydrolysates was significantly higher than without ultrafiltration or hydrolysis, which was indicated by the improvement of oxidation resistance compound by enzymatic hydrolysis (Yu et al, 2016). Therefore, the purified S. platensis protein in this study was directly digested by several proteolytic enzymes and filtrated to molecular weight cut off < 3 kDa.…”
Section: Antioxidant Activities Of S Platensis Protein Hydrolysatesmentioning
confidence: 99%
“…DPPH-free radical scavenging activity was measured according to the method described by Yu et al (2016) with some modification.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation